Optimalisasi Pola Asuh dan Sinergitas antara Orang Tua dan Guru Melalui Kegiatan Parenting di SD Negeri 2 Bulurejo Banyuwangi - Wanidha, Viena; Fitriatul Masruroh (Lembaga Pengembangan Kinerja Dosen, 2025)
Parenting is one way to improve parent’s understanding of their children. This parenting activity is a form of community service conducted at SD Negeri 2 Bulurejo Purwoharjo District Banyuwangi Regency. This parenting activity aims to improve parent’s understanding of parenting so that a good synergy is created between parents and school as the place of studying. This program is implemented in three stage; preparation, implementation, and the result evaluation. Lecture and also question and answer methods are applied to facilitate the sending of the information and understanding their responses related to the material. The result of the activities indicates significant changes; the process of educating now takes place in a warmer and more supportive environment. Teacher is not only becomes an educator, but also as a nurturing figure who understand children’s emotional needs. The parents also become more active and empathetic involvement in supporting their children’s growth and development, creating a positive synergy between family and school environment.